I Mille Piani delle migrazioni: Nomadismo, Barbarismo, Democrazia Molecolare - Mazzone, Stefania (SocietàMutamentoPolitica, 2020)
The essay wants to investigate the social, political, anthropological dimension of the vision of Deleuze and Guattari around the rhizomatic concept of migration starting from the elaboration of Mille piani. It reconstructs, as a priority, the definition of human mobility in a nomadic dimension, according to the interpretative keys of post-structuralism. So we compare the method with the concept of barbarism, to then identify the actuality of the definitions of war machine and molecular dimension of democracy with respect to the molar dimension of capital. It is a question of verifying, therefore, the overall timeliness of the elaboration of Deleuze and adjustments with respect to the theoretical problems posed by migrations understood not only historical sense but, above all, anthropological and social sense.